2018
DOI: 10.1186/s12889-018-6195-x
|View full text |Cite
|
Sign up to set email alerts
|

Mobilizing political support proved critical to a successful switch from tOPV to bOPV in Kano, Nigeria 2016

Abstract: BackgroundKano is one of the high-risk states for polio transmission in Northern Nigeria. The state reported more cases of wild polioviruses (WPVs) than any other state in the country. The Nigeria Demographic and Health Survey of 2013 indicated that OPV3 coverage in the routine immunization (RI) programmewas 57.9%. Additionally, serial polio seroprevalence studies conducted from 2011 to 2015 in the eightmetropolitan LGAs indicated low immunity levels against all three polio serotypes in children below one year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“… [38] , [39] , [40] , [48] , [57] , [58] , [75] , [76] , [36] Community factors Perception of vaccination Fears and misconceptions 14 Fears and misconceptions over vaccine safety and efficacy were associated with vaccination refusal and missed or incomplete schedules. [36] , [37] , [40] , [56] , [65] , [66] , [74] , [77] , [78] , [79] , [80] , [81] , [82] , [83] Community disapproval of vaccination 6 Vaccination refusal often clustered in settlements with similar ethnic and religious profiles. [45] , [53] , [62] , [66] , [84] , [85] Geographical factors Region (North vs South) 7 Northern Nigerian communities were less likely to be vaccinated compared to Southern Nigerian communities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… [38] , [39] , [40] , [48] , [57] , [58] , [75] , [76] , [36] Community factors Perception of vaccination Fears and misconceptions 14 Fears and misconceptions over vaccine safety and efficacy were associated with vaccination refusal and missed or incomplete schedules. [36] , [37] , [40] , [56] , [65] , [66] , [74] , [77] , [78] , [79] , [80] , [81] , [82] , [83] Community disapproval of vaccination 6 Vaccination refusal often clustered in settlements with similar ethnic and religious profiles. [45] , [53] , [62] , [66] , [84] , [85] Geographical factors Region (North vs South) 7 Northern Nigerian communities were less likely to be vaccinated compared to Southern Nigerian communities.…”
Section: Resultsmentioning
confidence: 99%
“…Studies suggested this was driven by higher levels of education and wealth in the South, higher proportions of Muslim households in the North, and greater insecurity in the North. [39] , [48] , [53] , [59] , [60] , [68] , [86] Setting (rural vs urban) 5 Rural areas typically had lower vaccination rates, and higher drop-out rates, compared to urban areas, although one sub-national study found the opposite [78] . [37] , [39] , [46] , [48] , [59] , [78] Cultural factors Religious affiliation 9 Muslim households were less likely to be vaccinated compared to Christian households.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses of high carbohydrate diets on genome wide gene expressions in animal models have provided valuable information on gene changes in response to excessive sugar intake, important for better understanding mechanisms at the molecular level [6][7][8][9][10][11]. Yet, the designs and/or the technologies used in most of reported investigations are limited.…”
Section: Introductionmentioning
confidence: 99%
“…In Kano, which is one of the states in the North West zone, full immunization coverage is only 10% and coverage with the third dose of pentavalent vaccine is 16% [8]. Kano is highly populated, and the persistently poor coverage level has made it a high-risk state for polio transmission [9, 10]. Several factors contribute to low immunization coverage among which are missed opportunities for vaccination (MOV) in health service settings [11–14].…”
Section: Introductionmentioning
confidence: 99%